Armenian Apocrypha relating to angels and biblical heroes - Stone, Michael E., 1938- (Early Judaism and its literature, 2016)
Michael E. Stone's latest book includes texts from Armenian manuscripts that are relevant to the development and growth of biblical themes and subjects. Most of these texts have not been published previously. Stone has collected a fascinating corpus of texts about biblical heroes, such as Joseph and Jonah, Nathan the Prophet, and Asaph the Psalmist. In addition, he has included documents illustrating particular points of the biblical story. This work reflects not just on how the Bible was interpreted in medieval times, but also how its stories and details were shaped by and served the needs of the vivid and creative Armenian spiritual tradition.